EFEKTIVITAS PENERIMAAN PAJAK KENDARAAN BERMOTOR PADA SAAT PANDEMI DI KANTOR SAMSAT II KOTA BANJARMASIN - Maulina Assiffa Pravita; Rusma Nailiah (Universitas Lambung Mangkurat, 2022)
This study aims to determine and analyze the effectiveness and constraints of accepting PKB during a pandemic at the Banjarmasin Samsat II Office. This study explains that the effectiveness in 2019 is at the percentage of 99.23% which is included in the effective category, in 2020 the percentage is 103.08% in the very effective category, and in 2021 the percentage is 90.88% in the effective category. In addition, the obstacles that occur are due to tax arrears or receivables and there are still many taxpayers who do not carry the requirements / do not understand the procedure for paying pkb using E-SAMSAT.